Ngajah duah sua : pameran pelukis-pelukis Sarawak = Exhibition of Sarawak artist. - Balai Seni Lukis Negara (Malaysia) (Kuala Lumpur: Balai Seni Lukis Negara, 2006)
Catalog of an exhibition held at Balai Seni Lukis Negara, Malaysia
Cover title
Exhibition held Apr. 1-June 25, 2006
Keywords: Art, Modern -- -- 21st century -- -- Malaysia -- -- Sarawak; Art, Modern -- -- 20th century -- -- Malaysia -- -- Sarawak